A New Rate-Dependent Constitutive Model of Superelastic Shape Memory Alloys and Its Simple Application in a Special Truss Moment Frame Simulation - Maria I. Ntina; Dimitrios S. Sophianopoulos (Advances in Civil Engineering)
In this work, a new constitutive model of the behavior of shape-memory alloys is presented, based on earlier models, showing a very good agreement with the existing experimental results. A simple approximate application concerning the use of these alloys modelled as dissipation devices in a special truss-moment frame is demonstrated. The results obtained are considered sufficiently encouraging as a motivation for the ongoing work.